Damage assessment of perforated steel beams subjected to blast loading. (June 2022) - Arafa, Ibrahim T.; Elhosseiny, Osama M.; Nawar, Mahmoud T.
Abstract: Despite the many studies that discussed the structural performance of steel beams with solid web subjected to blasts, the dynamic responses of steel beam with perforated web (PSBs) are not studied up under blast loads till now. In this research, the damage evaluation was numerically investigated under the combination of gravity and blast loading to simulate the realistic case of the external blast near PSBs. The damage indices that will be generated from the residual flexural and shear capacities could give an accurately express about the damage indices than the immediate deformation response after the direct blast shock. Extensive explicit FE analyses using LS-DYNA software are accomplished in order to examine the effects of several parameters including boundary conditions, web opening shapes, and strengthening techniques on toughness and the proposed damage index of the PSBs compared to the parent steel sections. From the comparative results, it was observed that PSBs provide a higher toughness in comparison to their parents through the overall stages of loadings. By changing the boundary condition from pinned to fixed ends, the deformations of PSBs decrease during blast shock directly, despite the toughness increases post the blast effects due to the catenary action that generated by the beam flanges. The beams with sinusoidal web openings and those with elongated circular shape get more toughness than other shapes in the case of fixed and pinned ends respectively. Furthermore, the strengthening strategy by continuous vertical stiffeners has a reliable improvement to get higher toughness in several levels of blast.